2022
DOI: 10.3389/fimmu.2022.907387
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 Modulation Strategies for Sepsis

Abstract: The triggering receptor expressed on myeloid cells-1 (TREM-1) is a pattern recognition receptor, which can be upregulated in inflammatory diseases as an amplifier of immune responses. Once activated, TREM-1 induces the production and release of pro-inflammatory cytokines and chemokines, in addition to increasing its own expression and circulating levels of the cleaved soluble extracellular portion of TREM-1 (sTREM-1). This amplification of the inflammatory response by TREM-1 has now been considered as a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 99 publications
(196 reference statements)
0
38
0
1
Order By: Relevance
“…Macrophages, which are radioresistant compared to neutrophils, potentially play a crucial role as innate immune cells for infections after radiation injury ( 5 ). TREM-1, a receptor expressed in myeloid cells, including macrophages, is upregulated in inflammatory diseases such as sepsis and its upregulation dysregulates the innate immune system, resulting in tissue injuries and poor prognosis ( 6 ). Therefore, we focused on TREM-1 expression on macrophages after radiation exposure and investigated the association between TREM-1 and prognosis in radiation injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages, which are radioresistant compared to neutrophils, potentially play a crucial role as innate immune cells for infections after radiation injury ( 5 ). TREM-1, a receptor expressed in myeloid cells, including macrophages, is upregulated in inflammatory diseases such as sepsis and its upregulation dysregulates the innate immune system, resulting in tissue injuries and poor prognosis ( 6 ). Therefore, we focused on TREM-1 expression on macrophages after radiation exposure and investigated the association between TREM-1 and prognosis in radiation injury.…”
Section: Discussionmentioning
confidence: 99%
“…The triggering receptor expressed on myeloid cells-1 (TREM-1) can be expressed on monocytes, macrophages, neutrophils, and dendritic cells. TREM-1 has been identified as a critical amplifier of inflammation to dysregulate immune response in various diseases ( 6 ). In septic patients, TREM-1 is upregulated on monocytes ( 7 ) and neutrophils ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these genes have been linked to ARDS and inflammation and consequently, cytokine storms, as highlighted in the table. Of particular interest is TREM-1, which has been previously reported to accentuate lung injury during ARDS and has shown promise as an inflammatory biomarker and as therapeutic target for sepsis and septic shock [ 26 , 27 ]. It has been reported to function in regulating T-cell proliferation and activation of antigen presenting cells during the antiviral immune response by amplifying toll-like receptor (TLR)-initiated responses against microbial challenges [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an AD model, TREM-1 facilitated microglial phagocytosis of amyloid beta (Aβ) [ 54 ]. Numerous preclinical experiments have demonstrated that TREM-1 inhibition can inhibit macrophage and microglia activation, thereby attenuating the inflammatory response [ 55 ]. The above studies suggest that microglial activation interacts with TREM-1 expression and that this action is at least partially dependent on NF-κB signaling.…”
Section: Introductionmentioning
confidence: 99%